Analisis Penerapan Sustainability Aspek Environmental Berdasarkan POJK No.51/POJK.03/2017 Pada Perusahaan Kelapa Sawit yang Terdaftar Pada Gabungan Pengusaha Kelapa Sawit Indonesia (GAPKI) - Br Hutasoit, Helen Ronauli; Situmorang, Aston L. (Universitas Methodist Indonesia, 2026)
The palm oil industry serves as one of Indonesia’s key economic pillars due to its contribution to foreign exchange earnings and employment. In line with POJK Number 51 on Sustainable Finance, companies in this sector are required to disclose sustainability reports that include environmental aspects. This study aims to analyze the level of environmental disclosure implementation in sustainability reports of palm oil companies that are members of the GAPKI during the 2021–2023 period. This research employs a quantitative descriptive method with a content analysis approach based on disclosure indicators regulated in POJK Number.51. Secondary data were obtained from annual and sustainability reports published on the official websites of GAPKI and each company. Of the 20 companies that issued sustainability reports, 13 were consistently reporting for three consecutive years and were selected as the research sample, totaling 39 observations. The results show a significant improvement in the quality of environmental disclosures from year to year. In 2021, most companies were categorized as partially applied, rising to well applied in 2022, and achieving fully applied in 2023. This trend reflects the growing awareness and commitment of palm oil companies to implement sustainable business practices in compliance with regulatory standards. Overall, the findings emphasize that environmental disclosure plays an important role as a form of corporate accountability and transparency to stakeholders, supporting sustainable development goals within Indonesia’s palm oil industry.